Selected Papers from the 3rd European Congress on Imaging Infection and Inflammation - Signore, Alberto; Sconfienza, Luca Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue is a collection of selected papers from the 3rd European Congress on Imaging Infection and Inflammation (www.nuclearmedicinediscovery.org/events.asp) and results of consensus sessions by major experts in the field including Nuclear Medicine physicians, Radiologists, Clinicians and microbiologists. The Journal of Clinical Medicine (JCM) provides an opportunity to publish data that were presented and discussed at the meeting in Rome in December 2019. One of the extremely important missions of this meeting was to present the recently published guidelines on diagnostic imaging of infections, and find a consensus agreement on some still controversial issues. With this in mind, the aim of the present Special Issue is to publish selected papers on: • Overviews on published guidelines • Review on recent development of diagnostic imaging of infections • Consensus document on the use of FDG and WBC in infections • Consensus document on the requirement for new radiopharmaceuticals for imaging bacteria